Workbook for English Drama by Incorporating Character Building for College Students - Yulieda Hermaniar (Jurnal Pendidikan Humaniora, 2015)
Abstract: Drama class in its relation to education gives mental and intellectual experience in mastering English as language and culture. As an authentic material, drama class in university level should explore students’ competence by providing varied material and activities. The development of a workbook by incorporating character building aspects for drama class in Lambung Mangkurat University is seen important. The workbook is developed by following the result of need assessment and the demand of course competenceof English Department in Lambung Mangkurat University. By involving 20 students of drama class, the research is carried out by following the modified stage of development by Borg and Gall. The result of the development shows that the developed workbook can be categorized as good product from the result of quantitative data in all aspects. Therefore, the workbook can be used as one of the component in teaching in the drama class. Key Words: workbook, english drama, character building